2006
DOI: 10.1016/j.ejvs.2006.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cine-CT Angiography for the Evaluation of the Thoracic Aorta; Insight in Dynamic Changes with Implications for Thoracic Endograft Treatment

Abstract: ECG-gated dynamic CTA with standard radiation dose is feasible on a 64-slice scanner and provides insight into (patho) physiology of thoracic aortic conformational changes. Clinicians typically oversize thoracic endografts by 10%. With aortic pulsatility resulting in diameter changes of up to 17.8%, the potential exists for endograft undersizing, graft migration, intermittent type I endoleak, and poor patient outcome. Furthermore, aortic pulsatility is not evenly distributed, and non-circular stentgraft design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 14 publications
1
88
1
1
Order By: Relevance
“…Aortic diameter varies in these patients by 10% (up to 18%) between systole and diastole. 145 In contrast to CTA, IVUS permits a dynamic real time evaluation of aortic diameters during the cardiac cycle. Furthermore, IVUS can easily detect the origin of side branches, allowing less use of contrast with DSA.…”
Section: Recommenda On 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic diameter varies in these patients by 10% (up to 18%) between systole and diastole. 145 In contrast to CTA, IVUS permits a dynamic real time evaluation of aortic diameters during the cardiac cycle. Furthermore, IVUS can easily detect the origin of side branches, allowing less use of contrast with DSA.…”
Section: Recommenda On 24mentioning
confidence: 99%
“…143 Most of the patients who undergo TEVAR for TAI are young. 144,145 These patients have a healthy and elastic aortic wall, with increased aortic pulsatile compliance. Aortic diameter varies in these patients by 10% (up to 18%) between systole and diastole.…”
Section: Recommenda On 24mentioning
confidence: 99%
“…Its non-invasive and inexpensive nature as well as its requiring less time in comparison with other detective techniques can be referred to as its advantages [5]. Taking a three dimensional image from all angles of a unit vascular complex is possible in this method [6]. Knowledge of variations in the branching pattern of the aortic arch is of great importance for patients who have to undergo four vessel angiography, aortic instrumentation, or supra aortic thoracic, head and neck surgery [7].…”
Section: Resultsmentioning
confidence: 99%
“…However, the dynamics of this motion are more subtle than the motions present in the heart itself. It has been shown that the order of magnitude of these motions is in the order of 2 mm [91,108]. It is reported that the limits of the motion that can be detected in clinical practice by ECG gating are slightly less than the spacing between the voxels (usually in the order of 0.5 mm), and that for a typical setup frequency components up to 2.7 Hz can be accurately detected [62].…”
Section: Applicationmentioning
confidence: 99%